GROSS UP BERMANFAAT DALAM TAX PLANNING ? - Nandhia Yossy Nareswari; Norman Duma Sitinjak (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2019)
Research on tax planning is mostly carried out until now because it is veryimportant for the company. Companies that have efforts to facilitate Income Tax Article 21 sometimes experience problems. The impact on the company is a fixed tax burden while the funds incurred increase. This study discusses tax planning that must be carried out by the company in an effort to facilitate Income Tax Article 21 so that corporate expenses for Income Tax Article 21 are recognized and employees get benefits namely take home pay not deducted Income Tax Article 21. The findings in this study are that the gross up method obtained Income Tax allowances which are equal to the 21 income tax payable, so the funds issued by the company to facilitate Income Tax Article 21 are recognized by the tax rules. Because the tax allowance is recognized as a burden,corporate income taxbecomes smaller and the employee take home pay does not decrease